The foreign vocabulary of the Qur'ān - Jeffery, Arthur. (Texts and studies on the Qurʼān, 2007)
Republication of Arthur Jeffery's important study, The Foreign Vocabulary of the Qur'ān , offers a new generation of scholars and students access to this foundational text. Arranged in Arabic alphabetical order, Jeffery's compendium of philological scholarship remains an indispensable tool for any serious study of Qur'ānic semantics. Drawing upon etymological examination of languages such as Greek, Persian, Syriac, Ethiopic, Coptic and Nabataean, Jeffery's work illuminates the rich linguistic texture of Islam's holy book. His lengthy introductory essay explores the exegetical analysis offered by medieval Muslim commentators as well as the insights provided by more recent research.